(untitled) (E Global Congress, 2025)
This academic thesis analyzes the main factors that affect the determination of the threshold amount of revenues and expenditures of local budgets. It explores the economic, legal, demographic, and institutional factors shaping the revenue side, as well as social needs, natural-geographical characteristics, and local governance policies that influence the expenditure level. The interdependence of these factors and the necessity of their consideration for ensuring local financial stability are substantiated. Practical proposals for more effective management of the local budget system are also developed.